Newborn screening for severe combined immunodeficiency using a novel and simplified method to measure T-cell excision circles (TREC) - Tagliaferri, Laura; Kunz, Joachim; Happich, Margit; Bruckner, Thomas; Hübschmann, Daniel; Okun, Jürgen G.; Hoffmann, Georg F.; Muckenthaler, Martina; Kulozik, Andreas (Clinical immunology, 2017)
The prognosis of children with severe combined immunodeficiency (SCID) depends on a presymptomatic diagnosis and early treatment before complications occur. We established and tested a simplified, practical and economic newborn screening method based on the quantification of T-cell receptor excision circles (TRECs) on dried blood spots (DBSs) through qPCR. Our method was validated by the analysis of 11 positive controls, which all showed an absence of TRECs, thus yielding a sensitivity of 100%. Further, we analyzed 6034 anonymized newborns of whom 6031 (99,95%) showed a normal TREC qPCR with a median of 600 estimated TREC copies/1.6mm punch. The test showed a recall-rate of 0.05%. We present a highly sensitive, specific and time- and cost-effective method of TREC quantification, which is suitable for SCID newborn screening. In comparison to established methods, our test requires only 25% of the input material, doesn't require DNA purification and significantly reduces time and cost requirement.
Available online 2 December 2016
Gesehen am 25.06.2018